ANALISIS DAN DESAIN PROSES BISNIS PERUSAHAAN DENGAN PENERAPAN BLUEPRINT DAN ASSESSMENT AS-IS VERSUS TO-BE (STUDY KASUS PADA SEBUAH PERUSAHAAN SWITCHGEAR DI BANTEN) - Ruhimat, Agus (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2020)
Financial reports that are always slow and inaccurate have a bad domino effect for the business, from starting prospective buyers to withdraw due to taking too long to get answers to inquiries, wrong selling prices due to incorrect recording costs, late incoming money due to late billing, and other internal operational constraints. Companies must immediately redesign the business processes, so they can operate more efficiently and increase productivity. Starting with setting clear objectives for the principles of change, followed by setting the intended Business Process Blueprint, and followed by a series of activities to identify the current process (As-Is) and define process objectives (To-Be), a new Business Process Design is obtained. reflects the flow of business processes that integrate all functions of the company. The integration of business processes has succeeded in making the process simpler with a focus on the flow of cash-in and cash-out processes as well as internal management which can be directly seen on the General Ledger to make it easier to make timely financial reports and correct costing costs and other important business decisions. Keywords: Design Process, Manufacturing Process Flow, ERP.